Changes in Metabolically Active Bacterial Community during Rumen Development, and Their Alteration by Rhubarb Root Powder Revealed by 16S rRNA Amplicon Sequencing - Wang, Zuo; Elekwachi, Chijioke; Jiao, Jinzhen; Wang, Min; Tang, Shaoxun; Zhou, Chuanshe; Tan, Zhiliang; Forster, Robert J. (Frontiers in Microbiology, 2017)
The objective of this present study was to explore the initial establishment of metabolically active bacteria and subsequent evolution in four fractions: rumen solid-phase (RS), liquid-phase (RL), protozoa-associated (RP), and epithelium-associated (RE) through early weaning and supplementing rhubarb root powder in 7 different age groups (1, 10, 20, 38, 41, 50, and 60 d) during rumen development. Results of the 16S rRNA sequencing based on RNA isolated from the four fractions revealed that the potentially active bacterial microbiota in four fractions were dominated by the phyla Proteobacteria, Firmicutes, and Bacteroidetes regardless of different ages. An age-dependent increment of Chao 1 richness was observed in the fractions of RL and RE. The principal coordinate analysis (PCoA) indicated that samples in four fractions all clustered based on different age groups, and the structure of the bacterial community in RE was distinct from those in other three fractions. The abundances of Proteobacteria decreased significantly (P < 0.05) with age, while rises in the abundances of Firmicutes and Bacteroidetes were noted. At the genus level, the abundance of the predominant genus Mannheimia in the Proteobacteria phylum decreased significantly (P < 0.05) after 1 d, while the genera Quinella, Prevotella, Fretibacterium, Ruminococcus, Lachnospiraceae NK3A20 group, and Atopobium underwent different manners of increases and dominated the bacterial microbiota across four fractions. Variations of the distributions of some specific bacterial genera across fractions were observed, and supplementation of rhubarb affected the relative abundance of various genera of bacteria.